Fungsi Pastoral Konseling dalam Tradisi Lisan Aimpalukka bagi Pemuda di Talaud - Viena Bella Taarega; Agnes Relly Poluan; Sugijanty Supit (PT. Giat Konseling Nusantara, 2024)
Aimpalukka is one of the various traditions of the Talaud region which has a pastoral counseling function. The pastoral counseling functions in this tradition are very useful for youth life in solving the problems faced by youth. The function of Pastoral counseling in the aimpalukka tradition is to help strengthen, reconcile and support the young generation who are in trouble. But the younger generation does not understand and does not realize how important this tradition is in their lives. The method used in this research is descriptive qualitative which seeks to describe a social phenomenon and outline the function of pastoral counseling from the aimpalukka tradition for young people in Talaud with the aim of showing how important the value and meaning of the aimpalukka tradition is for the young generation in Talaud.